Use of sutimlimab to manage anemia in a patient with high‐grade B ‐cell lymphoma and complement binding anti‐ AnWj autoantibody - Kathy Haddaway; Sri Bharathi Kavuri; Nikhil Ranjan; Jireh Oncita; Cole Sterling; Michael Cole; Matthew Lankiewicz; Robert Brodsky; Aaron A. R. Tobian; Elizabeth P. Crowe; Gloria Gerber (Transfusion, 2026)
Abstract Background Anti‐AnWj autoantibody production with concomitant antigen suppression rarely has been reported secondary to lymphoid malignancy. Anti‐AnWj autoantibodies are often considered clinically insignificant; however, cases of posttransfusion hemolysis have been documented which require transfusion of AnWj‐negative red blood cells (RBC). AnWj‐negative RBC units are rare, thus options for long‐term transfusion are limited. We report the novel use of sutimlimab, a classical complement pathway inhibitor, for severe anemia in a patient with a complement fixing anti‐AnWj autoantibody. Case Presentation A 57‐year‐old male with high‐grade B‐cell lymphoma presented with severe anemia and was found to have an anti‐AnWj autoantibody of IgM and IgG isotypes and a complement‐positive direct antiglobulin test. AnWj‐positive RBC were provided for transfusion. His hemoglobin did not augment, and he developed evidence of hemolysis following crossmatch‐incompatible RBC units. Transfusion of In(Lu) RBC showed initial response; however, his anemia persisted. Sutimlimab was subsequently initiated based on the complement fixing ability of the autoantibody. An improvement in hemoglobin, decrease in lactate dehydrogenase, and decrease in RBC‐bound complement fragments were observed following sutimlimab administration. Conclusion Management strategies for clinically significant anti‐AnWJ are not well defined. To our knowledge, this is the first case using sutimlimab to manage complement‐mediated hemolysis due to an auto‐anti‐AnWj antibody. While initial response to sutimlimab was favorable, the patient's comorbid lymphoma, multiple therapies, and short treatment period limit definitive conclusions regarding efficacy. Anti‐complement therapy warrants further study for refractory antibody‐mediated hemolysis with evidence of complement activation in the absence of compatible transfusions.